Assessment of tumour response in a rat rhabdomyosarcoma. - Curtis, S. B. (Nature Publishing Group, 1980)
A rhabdomyosarcoma in a WAG/Rij rat with capacity for colony growth after tumour excision and enzymatic dissociation has been used to study response to high and low LET radiation. End points are tumor volume response, TCD50/180, clonogenic capability after tumour irradiation in situ, and in vitro cell survival after irradiation in both the well-oxygenated and the hypoxic conditions. Experience has shown that sublines with different growth rates, radiosensitivity and plating efficiency can arise from the same frozen stock. The conclusions that can be drawn from an analysis of the data obtained to date are as follows: 1. There is no correlation between the doubling times of our two cell lines growing in culture and in the animal. 2. RBE values obtained from growth delay and from TCD50 end points are in fair agreement. 3. Cell survival curves obtained after in situ irradiation show the cells to be more radioresistant than cells irradiated in suspension in vitro. 4. RBE values for cell survival after in situ irradiation compare favourably with those obtained both for tumour growth delay and in vitro cell survival. 5. Not enough is known at present about radiation-altered cell kinetics to develop a self-consistent model of tumour response after irradiation.